Papua New Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
This paper analyzes the workings and effectiveness of the monetary transmission mechanism in Papua New Guinea. The paper is organized as follows: it describes the current institutional structure in Papua New Guinea; interest rate is discussed; the evidence from vector autoregression analysis on the relationship between monetary policy variables and output and prices is considered; finally, implications are included. The Bank of Papua New Guinea (BPNG) uses a reserve money framework to conduct monetary policy operations. A macroeconomic balance approach estimates the REER, which simultaneously achieves internal and external balance.